2022
DOI: 10.1021/acsagscitech.1c00292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet Light Exposure and Compost Tea Supplementation on Growth, Antioxidant Activities, and Microbiome of Hydroponically Grown Mustard Greens

Abstract: Hydroponic food production in greenhouses is challenged by reduced exposure to ultraviolet (UV) light and beneficial soil microorganisms, which predisposes plants to antioxidant deficiencies and disease susceptibility. The objective of this study was to investigate the effects of UV light exposure and compost tea treatment on hydroponically grown plants. Garnet Giant mustard greens were hydroponically grown in both indoor and outdoor greenhouse settings, with and without UV light blocking and supplementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…This indicates that increasing the percentage of compost leads to a decrease in anthocyanins. In this respect, the application of compost tea on hydroponic mustard leaves [ 36 ], and vermicompost on fenugreek plants [ 37 ], reduced anthocyanin content, compared to control treatments; fact that it could be reported through anthocyanin synthesis was inhibited by nitrogen increase [ 38 ], which corresponds to the results we have obtained with higher proportion of compost in the growing media combination, that showed higher amount of nitrogen ( Table 1 ; Table 5 ; Table 6 ).…”
Section: Resultssupporting
confidence: 68%
“…This indicates that increasing the percentage of compost leads to a decrease in anthocyanins. In this respect, the application of compost tea on hydroponic mustard leaves [ 36 ], and vermicompost on fenugreek plants [ 37 ], reduced anthocyanin content, compared to control treatments; fact that it could be reported through anthocyanin synthesis was inhibited by nitrogen increase [ 38 ], which corresponds to the results we have obtained with higher proportion of compost in the growing media combination, that showed higher amount of nitrogen ( Table 1 ; Table 5 ; Table 6 ).…”
Section: Resultssupporting
confidence: 68%
“…The organic waste ingested by earthworm provides energy for microbial growth (Ravindran et al, 2016 ). Lu et al ( 2022 ) experimentally confirmed that in the absence of UV blockage, VCT supplementation promoted nitrogen and mineral accumulation in mustard plant, increased beneficial bacteria, and reduced fungal pathogens. Therefore, adding VCT can influence the microbial community and promote plant growth.…”
Section: Resultsmentioning
confidence: 96%
“…The influence of compost tea from Oyster Mushroom Waste on the growth and the flavonoid content in the black rice was evaluated by Khoerunnisa et al [71]; the results displayed an increase in both the growing rate and flavonoid content depending on the treatments administered to the plants, in particular it was showed that the administration of compost tea of 45% lead to best rice growth, while the concentration of 35% lead to a best flavonoids content [71]. An example of the combined use of compost tea with other treatments is given by Lu et al [72], who investigated how hydroponically grown plants respond to UV light exposure and compost tea treatment. Garnet Giant mustard greens were grown both indoors and outdoors, with or without UV light blocking and with or without the addition of compost tea.…”
Section: Influence Of Compost Tea On Nutrients and Bioactive Componen...mentioning
confidence: 99%
“…The mustard greens' antioxidant capacities increased with increased UV exposure, while being supplemented with compost 9 of 13 tea decreased their antioxidant capacities. Treatment with compost tea enhanced good bacteria and lowered pathogenic fungi [72]. The impact of organic fertilizer solutions on the productivity, quality, and antioxidant capacity of hydroponically grown cucumber (Cucumis sativus L.) fruits produced in a greenhouse has been studied by Santiago-López et al [73].…”
Section: Influence Of Compost Tea On Nutrients and Bioactive Componen...mentioning
confidence: 99%
See 1 more Smart Citation